21 Comparison of Savanna, Kiko, and Spanish Sires for Meat Goat Doe-Kid Traits. (28th November 2020) - Stevens, Lauren; Hayes, Emily G; Khanal, Piush; Thomas, Shaneqwa; Byars, Mozell; Browning, Richard
Abstract: Savanna sires were evaluated for kid preweaning and doe reproductive traits over six years. Savanna (n = 17) and Kiko (n = 13) sires were bred to Kiko-base does producing 600 kids. Savanna (n = 17) and Spanish (n = 11) sires were bred to Spanish-base does producing 456 kids. Doe traits were evaluated on 536 Kiko and 441 Spanish doe exposures. Kids were weighed at birth and when weaned at 3 mo of age. Non-genetic factors sex and litter size influenced (P < 0.05) kid performance traits as expected. Birth weights of kids from Kiko does were heavier (P < 0.01) for Savanna sires than Kiko sires (3.11 vs. 2.83 ± 0.08 kg). Birth weights of kids from Spanish does were heavier (P < 0.01) for Savanna sires than Spanish sires (3.05 vs. 2.76 ± 0.09 kg). Sire breed did not affect (P < 0.05) weaning weight from Kiko does (15.0 vs 14.8 ±0.6 kg). Savanna sires generated heavier (P < 0.05) weaning weights than Spanish sires (14.2 vs. 13.3 ± 0.6 kg) from Spanish does. Sire breed did not affect ADG or kid survival rates in either doe group. Non-genetic factors litter size and age of dam affected (P < 0.05) doe performance traits in both doe groups. Savanna sires produced heavier litters (P < 0.01) at birth compared to Kiko sires on Kiko does (10.7 vs. 9.7 ± 0.4 kg) and compared to Spanish sires on Spanish does (9.4 vs. 8.3 ± 0.5 kg). Service sire breed did not affect kidding or weaning rate, number of kids born or weaned, or litter weaning weight in either doe group. Savanna sires consistently increased birth weight values. Sire breed did not consistently affect weaning weight values and did not influence other preweaning kid traits or doe reproductive traits.